Improving the Efficiency of the Use of Renewable Energy in the Energy Sector - Samiev Shakhrukh (Journal of Higher Education and Academic Advancement, 2024)
This scientific article explores the reforms and their results in improving the efficiency of the use of renewable energy in the electricity sector, the problems that persist in the network, the problems in the regulation and management of the electricity sector, and offers and recommendations on ways to eliminate them.